2018
DOI: 10.1163/15685403-00003775
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of Eurycarcinus A. Milne-Edwards, 1867 (Decapoda, Brachyura, Pilumnidae)

Abstract: The taxonomy of the intertidal pilumnid crabEurycarcinusA. Milne-Edwards, 1867 is reviewed in the present work. Characters that defineEurycarcinusand distinguish it from the allied generaHeteropanopeStimpson, 1858,PilumnopeusA. Milne-Edwards, 1867, andBenthopanopeDavie, 1989 are discussed.Eurycarcinuscan be distinguished from these genera by the smooth features of the carapace, shape and form of the male pleon, and structure of the male thoracic sternum, notably the shapes of sternites 1-4 and whether sternite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…The specimens examined are deposited in the Zoological Reference Collection, Department of Life Sciences, Hemchandracharya North Gujarat University, Patan, Gujarat, India (LFSc.ZRC); Zoological Survey of India, Kolkata, India (ZSI); and the Zoological Reference Collection of the Lee Kong Chian Natural History Museum, National University of Singapore (ZRC). The terminology used in the description follows Davie et al (2015) and Ng et al (2018). The following abbreviations are used: CL = carapace length; CW = carapace width; G1 = male first gonopod; G2 = male second gonopod; coll.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The specimens examined are deposited in the Zoological Reference Collection, Department of Life Sciences, Hemchandracharya North Gujarat University, Patan, Gujarat, India (LFSc.ZRC); Zoological Survey of India, Kolkata, India (ZSI); and the Zoological Reference Collection of the Lee Kong Chian Natural History Museum, National University of Singapore (ZRC). The terminology used in the description follows Davie et al (2015) and Ng et al (2018). The following abbreviations are used: CL = carapace length; CW = carapace width; G1 = male first gonopod; G2 = male second gonopod; coll.…”
Section: Methodsmentioning
confidence: 99%
“…and Gosavi et al (2017) recorded Heteropanope glabra Stimpson, 1858, and Pilumnopeus convexus (Maccagno, 1936), respectively, from India. Ng et al (2018) revised Eurycarcinus, and distinguished it from Heteropanope by the following characters: thoracic sternite 8 remains clearly exposed when the male pleon is closed, male pleonal somite 3 is proportionately wider with the lateral margin distinctly projecting on lateral side, and male thoracic sternites 3 and 4 are transversely wider with the sterno-pleonal cavity close to the margin between sternites 3 and 4. On the basis of the published figures of Deb (1995Deb ( , 1999, Ng et al (2018) suggested that E. bengalensis can be assigned to Heteropanope on the basis of carapace shape but was uncertain about H. neolaevis because its gonopod structure was atypical for the genus.…”
Section: Eurycarcinus Bengalensismentioning
confidence: 99%
See 2 more Smart Citations
“…Ng et al (2008: 204) transferred Nectopanope to Xanthinae (Xanthidae) without explanation. This was necessary as Heteropanope and Eurycarcinus had already been moved to the Pilumnidae (present Pilumnoidea) by then (see Ng et al 2018).…”
Section: Systematicsmentioning
confidence: 99%